When pride still mattered a life of Vince Lombardi - Maraniss, David (New York Simon & Schuster, 1999)
More than any other sports figure, Vince Lombardi transformed football into a metaphor of the American experience. The son of an Italian immigrant butcher, Lombardi toiled for twenty frustrating years as a high school coach and then as an assistant at Fordham, West Point, and the New York Giants before his big break came at age forty-six with the chance to coach a struggling team in snowbound Wisconsin.
Includes bibliographical references (p. [517]-518 )
Keywords: Lombardi, Vince